2020
DOI: 10.1093/ofid/ofaa459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrase Inhibitor–Based ART on the NLRP3 Inflammasome Among ART-Naïve People With HIV

Abstract: The NLRP3 inflammasome, activated in the setting of HIV, contributes to pro-atherogenic inflammation. Among ART-naïve PWH (vs. controls), levels of caspase-1 – a key component of the NLRP3 inflammasome – were significantly increased. Six months of elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate significantly decreased caspase-1 levels in association with CD4+/CD8+ ratio recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Tan et al [ 25 ] showed that increased inflammatory vesicle activation and upregulation of caspase-1, IL-1 β , and NLRP3 levels in up to 25% of HIV/tuberculosis-coinfected patients triggered an excessive inflammatory response after antiretroviral therapy (ART) initiation. Toribio et al [ 26 ] similarly demonstrated that caspase-1 levels were significantly elevated in ART-treated HIV patients compared to controls, which in turn promoted an increase in NLRP3 inflammatory vesicles. CD4+ T cells in pyroptosis releasing proinflammatory cellular inclusions including ATP may provide a second inflammatory stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al [ 25 ] showed that increased inflammatory vesicle activation and upregulation of caspase-1, IL-1 β , and NLRP3 levels in up to 25% of HIV/tuberculosis-coinfected patients triggered an excessive inflammatory response after antiretroviral therapy (ART) initiation. Toribio et al [ 26 ] similarly demonstrated that caspase-1 levels were significantly elevated in ART-treated HIV patients compared to controls, which in turn promoted an increase in NLRP3 inflammatory vesicles. CD4+ T cells in pyroptosis releasing proinflammatory cellular inclusions including ATP may provide a second inflammatory stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Six months of treatment with an INSTI-based ART regimen can significantly reduce plasma caspase-1 levels in ART-naïve PLHIV [ 26 ], and newly initiated ART reduces the percentage of circulating CD4+ T cells expressing caspase-1 [ 40 ]. Such studies assess the importance of the specific effects of different treatment regimens on chronic inflammation and IA.…”
Section: Introductionmentioning
confidence: 99%
“…PWH before ART show a higher level of caspase-1 compared to people without HIV. ART decreases caspase-1 levels but they still tend to be higher than people without HIV, indicating that there is still inflammation and activation of NLRP3 inflammasome [14]. Combination ART use is associated with a 26% relative increase in the rate of myocardial infarction (MI) per year of exposure to ART [25].…”
Section: Discussionmentioning
confidence: 99%
“…The same study found a correlation between the NLRP3 inflammasome and coronary artery plaque composition and severity in PWH on ART. In a collaborative study [14], we showed that PWH who have not received ART compared to uninfected controls have higher levels of plasma caspase-1, a component of the NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 96%
“…These drugs, together with the new analogues of hydroxychloroquine, can form an interesting set of compounds for further investigations [ 92 ]. Due to similar links to inflammation, NLRP3 inflammasome activation, and Panx1-related infectious diseases, the proposed group of drugs could hold great potential to uncover additional Panx1 channel inhibitors [ 93 , 94 , 95 , 96 , 97 , 98 ]. To conclude, three new Panx1 channel inhibitors were identified from a panel of drugs formerly repurposed for the treatment of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%